Dental abnormalities of the southern thorny skate Amblyraja doellojuradoi (Chondrichthyes, Rajidae) - Delpiani, Gabriela Elina (2012)
Teeth morphology has been widely used in taxonomic, biological and fossil teeth studies of Chondrichthyes. Herein, dental abnormalities in Amblyraja doellojuradoi are described. Almost 10% of 182 specimens sampled presented any of these types of dental anomalies: (1) an additional incomplete tooth row between two complete rows, (2) an increasing tooth base size and division of its cusps until the complete splitting of teeth in the same row, and (3) an irregular tooth arrangement on the right side of the lower jaw. Possible causes producing these malformations such as mutation, damage by feeding or reproductive behavior are discussed.